Struggle for domination in the Middle East : the Ottoman-Mamluk War, 1485-91 - Har-El, Shai. (Leiden ; New York : E.J. Brill, 1995)
This two-part volume offers a comprehensive account of the conflict between the Ottoman and Mamluk Empires. Part One explores Ottoman-Mamluk relations from their inception in the middle of the fourteenth century to the laying of the foundations of the conflict in the second half of the fifteenth century. Part Two offers a detailed description of the actual war of 1485-91, and analyzes it from various angles including military, economic, and diplomatic. Based largely on Ottoman, Mamluk and Italian primary sources - documentary and narrative - the volume helps to understand the second and final war between the Ottomans and Mamluks in 1516-17, which resulted in the downfall of the Mamluk Empire and the firm establishment of Ottoman power in the Middle East.
Pt. 1. The Struggle for Southeastern Anatolia. I. The Mamluk Frontier Policy in Anatolia. II. Harmony and Conflict in Early Ottoman-Mamluk Relations. III. The Struggle for Karaman and Dulkadir (1464-81). IV. Prelude to the War (1481-85) -- Pt. 2. The First Ottoman-Mamluk War. V. Ottoman Invasions of Cilicia (1485-87). VI. Contest in the Diplomatic Arena (1486-88). VII. The Battle of Aga-Cayiri (1488). VIII. The Close of the War (1489-91) -- App. 1. Sources on the Second Ottoman-Mamluk War -- App. 2. Description of the Ottoman Fleet by Tursun Beg -- App. 3. Venetian Intelligence Report on the Ottoman Fleet -- App. 4. Rhodian Report on the Ottoman-Mamluk War.
Includes bibliographical references (p. [224]-232) and index.
Keywords: Turkey -- History -- Bayezid II, 1481-1512.